Fiqh Muamalah: Hukum Jual Beli dalam Islam - Fadilatunnisa, Nur; Hidayati, Aidha; Carlos, Juanda; Azzait, Rohmat; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
A very common form of business in society is buying and selling. In muamalah fiqh, the law of buying and selling itself is defined as “buying and selling”, which in fiqh terms is referred to as “al-bai”, which means “selling, replacing, and exchanging something for something else”. The purpose of this research is to discuss the problems and solutions of cases related to the law of buying and selling in Islam. This research method uses a type of qualitative research through literature study by applying content analysis that focuses on library data, such as books, journals, archives, and so on. The results of this research related to the law of buying and selling in Islam are a solution to many forms of contemporary buying and selling that violate sharia, such as price manipulation, fraud, and selling goods that do not exist. Consequently, in order to ensure that buying and selling transactions are Shariah-compliant, an in-depth understanding of Islamic law and the application of that law in specific contexts is required. It is hoped that these findings will help strengthen a just and sustainable Islamic economic system.